Evaluation of polyurethane resin injection for concrete leak repair. (December 2019) - Safan, Mohamed A.; Etman, Zeinab A.; Konswa, Alaa
Abstract: The aim of this study is to evaluate the effectiveness of water leakage treatment using polyurethane resin injection for concrete structure elements. Water leakage may have destructive effects on building structures. Leaks may be attributed to several factors, such as the use of an inadequate waterproofing system, inadequate design, poor concrete quality, and poor workmanship. A wide range of techniques and products are employed to control water intrusion, including resin injection, which is among the methods commonly used for resolving leakage in waterproofing systems. The aforementioned techniques and products also provide special solutions for other construction problems. In this study, the effectiveness of using resin injection to stop water leakage is investigated. As part of the experimental work, two water tanks are modelled to simulate actual field conditions. The tanks are filled with pumped water, and three measured water pressure values are investigated to determine the effectiveness of resin injection method. The water pressure is gradually increased up to 3 bar (43.5 psi) for three days, and relevant pressure reductions are determined in each case. The results indicate that the ability of concrete elements to resist water flow is inadequate when a waterproofing system is not employed (Case 1); however, concrete permeability is slightly reduced when waterproofing materials are used (Case 2). More specifically, the use of polyurethane resin injection can substantially stop water leaks (Case 3). Polyurethane resins are designed to expand with water to permanently block the passage of water through cracks or voids. Their fast expansive reaction with water forms a tough and flexible/elastic foam. The analysis demonstrates the reduction in concrete permeability after the application of polyurethane resin injection. The results obtained in this research can be utilised as a solution to stop water leaks and cracks in concrete elements, such as basement walls, manholes, tunnels, storm sewers, retaining walls, seawalls, dams, below-grade parking decks, water treatment tanks, elevator pits, box culverts, below-grade vaults, walls, pits, and floors.